The study of correlation between thyroid function and blood pressure in hypertensive patients attending out patient department in tertiary care centre - Patange, Aparna; Shah, Harsh; Vora, Harshil (International Journal of Research in Medical Sciences, 2020)
Background: Hypertension may be the initial clinical presentation for at least 15 endocrine disorders, including overt and subclinical hyperthyroidism and hypothyroidism. The correction of thyroid dysfunction may normalize Blood Pressure (BP) in most cases, therefore checking thyroid function is essential during the workup for hypertension. The present study was conducted to find out the association between hypertension and thyroid dysfunction. Methods: It was a retrospective, observational study conducted among patients having hypertension visiting the outpatient department of Medicine in KIMS Karad, during the period of 2 months. Results: The mean values of various thyroid function parameters among hypertensive cases was assessed in the current study, Authors found that the mean Serum T3 level was 93.5917±32.82, Mean Serum T4 level was 6.72±1.64 and the mean Serum TSH level was 2.52±2.71. Among all the cases about 52% cases had deranged thyroid function reports. Conclusions: The results of this study suggest an association between subclinical hypothyroidism and increased blood pressure levels.